2013
DOI: 10.5194/bg-10-2897-2013
|View full text |Cite
|
Sign up to set email alerts
|

Combining a coupled FTIR-EGA system and in situ DRIFTS for studying soil organic matter in arable soils

Abstract: An optimized spectroscopic method combining quantitative evolved gas analysis via Fourier transform infrared spectroscopy (FTIR-EGA) in combination with a qualitative in situ thermal reaction monitoring via diffuse reflectance Fourier transform infrared spectroscopy (in situT DRIFTS) is being proposed to rapidly characterize soil organic matter (SOM) to study its dynamics and stability. A thermal reaction chamber coupled with an infrared gas cell was used to study the pattern of thermal evolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Oxidation of graphite upon heating could result in specific infrared absorption bands (Tan et al, 2013), which nevertheless would still be superimposed by SOM-specific bands in natural soil samples. As discussed by Demyan et al (2013), not only the available oxygen but also the heating rate has an important effect on the charring of OM and thereby on the thermal and spectral properties of the studied material.…”
Section: Potential For Combining Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Oxidation of graphite upon heating could result in specific infrared absorption bands (Tan et al, 2013), which nevertheless would still be superimposed by SOM-specific bands in natural soil samples. As discussed by Demyan et al (2013), not only the available oxygen but also the heating rate has an important effect on the charring of OM and thereby on the thermal and spectral properties of the studied material.…”
Section: Potential For Combining Methodsmentioning
confidence: 95%
“…An interesting observation was the similar predicted graphite content in calibration set 1 by both the FTIR and TGA methods, especially as FTIR is based on spectral properties and TGA on the thermal stability of the graphite. It has previously been suggested to combine FTIR and TGA systems to rapidly characterize the soil OM (Demyan et al, 2013). Oxidation of graphite upon heating could result in specific infrared absorption bands (Tan et al, 2013), which nevertheless would still be superimposed by SOM-specific bands in natural soil samples.…”
Section: Potential For Combining Methodsmentioning
confidence: 99%
“…Oxidation of graphite upon heating could result in specific infrared bands (Tan et al, 2013), which nevertheless would still be superimposed by SOM-specific bands in natural soil samples. As discussed by Demyan et al (2013), not only the available oxygen, but also the heating rate has an important effect on the charring of OM and thereby on the thermal and spectral properties of the studied material.…”
Section: Potential For Combining Methodsmentioning
confidence: 95%
“…An interesting observation was the similar predicted graphite content in calibration set 1 by both the FTIR and TGA methods, especially as FTIR is based on spectral properties and TGA on the thermal stability of the graphite. It has previously been suggested to 20 combine FTIR and TGA systems to rapidly characterize the soil OM (Demyan et al, 2013). Oxidation of graphite upon heating could result in specific infrared bands (Tan et al, 2013), which nevertheless would still be superimposed by SOM-specific bands in natural soil samples.…”
Section: Potential For Combining Methodsmentioning
confidence: 99%
“…3). It was previously suggested that the high SOC storage capacity of this site is a result of cation-bridging due to a high content of adsorbed cations (Ellerbrock and Gerke, 2018). Additionally, there is evidence of black carbon at the site (e.g., the high thermal stability found by Demyan et al, 2013).…”
Section: How Useful Is the Drifts Stability Index?mentioning
confidence: 93%